1994
DOI: 10.1111/j.1464-5491.1994.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Admissions and Social Deprivation of Patients with Diabetes Mellitus

Abstract: This study examined the relationship between hospital admissions for patients with diabetes mellitus and residence in an area of social deprivation. Admissions of patients with diabetes mellitus were identified during a 5-year period between 1987 and 1992 using the district patient information service. All persons admitted were assigned to an electoral ward on the basis of their postcode. Age standardized admission rates were compared to the Townsend Deprivation Score for each electoral ward. A positive correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Others have shown that the risk of heart disease is higher in more deprived groups (22) and that the rate of hospital admissions also is higher in people who lived in deprived areas (23). However, these studies were ecological analyses of people with mainly NIDDM, and they did not examine the two sexes separately.…”
Section: Results-mentioning
confidence: 98%
“…Others have shown that the risk of heart disease is higher in more deprived groups (22) and that the rate of hospital admissions also is higher in people who lived in deprived areas (23). However, these studies were ecological analyses of people with mainly NIDDM, and they did not examine the two sexes separately.…”
Section: Results-mentioning
confidence: 98%
“…This suggests that characteristics of practices in deprived areas, other than those we measured in our study, have an important influence on control of diabetes. The higher prevalence of diabetes in practices in deprived areas [21], coupled with an increased prevalence of risk factors for cardiovascular disease [22,23], greater morbidity [24] and mortality [25] amongst those with diabetes, poorer access to services such as chiropody and dietetics [26] and a reduced likelihood of patients attending for diabetic reviews [7], clearly illustrates the difficulties facing primary healthcare teams in providing diabetic care to deprived populations. In addition, there may be other patient level factors that we were unable to measure that may be important determinants of glycaemic control, such as lower educational level which was associated with poorer diabetic control in a recent study in the Netherlands [6].…”
Section: Discussionmentioning
confidence: 99%
“…A complex range of self-care behaviors is required to manage diabetes, among them dietary restrictions, regular exercise, adherence to and management of multiple medications and dosing schedules, SMBG, periodic examination of the feet, and maintaining glycemic control during intercurrent illness. Among adults with diabetes, studies associate minority race/ethnicity, low income, less education, and living in a poverty area with higher rates of smoking (322)(323)(324)(325), lower rates of SMBG (326 -329), less vigorous exercise (322,324,330,331), poorer adherence to medications (332), and underuse of recommended preventive health screening (333,334).…”
Section: Individual Risk Behaviorsmentioning
confidence: 99%